A contribution to the Slovenian spider fauna – III - Žan Kuralt; Rok Kostanjšek (Natura Sloveniae)
The study reports on first records of two spider species for Slovenian fauna, Zodarion rubidum and Prinerigone vagans from the Bela krajina region in southeastern Slovenia. Regarding their presence in the neighbouring countries and distribution in Europe, both species could be considered as expected. The finding of Z. rubidum during night time in the urban area demonstrates negligence of sampling at unconventional time and in anthropogenic habitats. Finding two new records during short term field survey also indicates undersampling of the spider fauna and supports the need for further faunistic work in the field of arachnology.